Synthesis and structural characterization of perovskite YFeO3 by thermal decomposition of a cyano complex precursor, Y[Fe(CN)6]·4H2O - Gil, D.M. (2010)
Fil: Guimpel, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina